2014
DOI: 10.5489/cuaj.2016
|View full text |Cite|
|
Sign up to set email alerts
|

Oncological and functional outcomes of 722 robot-assisted radical prostatectomy (RARP) cases: The largest Canadian 5-year experience

Abstract: Introduction: While RARP (robotic-assisted radical prostatectomy) has become the predominant surgical approach to treat localized prostate cancer, there is little Canadian data on its oncological and functional outcomes. We describe the largest RARP experience in Canada. Methods: Data from 722 patients who underwent RARP performed by 7 surgeons (AEH performed 288, TH 69, JBL 23, SB 17, HW 15, QT 7, and KCZ 303 patients) were collected prospectively from October 2006 to December 2013. Preoperative characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…In general population, potency recovery rate at one year after the surgical procedure was assessed ranging from 29.6% to 77.6% (33, 34). In the current study 6 patients (66.7%) received a nerve-sparing procedure (4 bilateral, 2 monolateral), and 5 (55.6%) achieved a potency recovery, with or without PDE5i intake, sufficient to have sexual intercourses.…”
Section: Discussionmentioning
confidence: 99%
“…In general population, potency recovery rate at one year after the surgical procedure was assessed ranging from 29.6% to 77.6% (33, 34). In the current study 6 patients (66.7%) received a nerve-sparing procedure (4 bilateral, 2 monolateral), and 5 (55.6%) achieved a potency recovery, with or without PDE5i intake, sufficient to have sexual intercourses.…”
Section: Discussionmentioning
confidence: 99%
“…After 3, 6 and 12 months, results were 57%, 63% and 82%, respectively (23). Using SHIM ( Sexual Health Index for Men ) questionnaire, a Canadian study with 722 cases reported recovery of sexual potency in 1, 3, 6 and 12 months of 19.5%; 31.4%; 37.2% and 52.4% (24).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, RARP has been demonstrated as a safe procedure with acceptable oncological and functional outcomes with benefits of shorter hospital stay, convalescence and blood loss as the forefront of reduced morbidity. 9 The current guidelines define BCR as a rising PSA after surgery with two documented consecutive rises over the value of 0.2 ng/ml. 10 Radiotherapy represents a curative therapeutic option that can be offered to men with postoperative detectable PSA.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of RARP, the weighted mean potency rate and the mean rate of urinary continence (no-pad) at 24 months were 64.9% and 91.4%, respectively. 9 In spite of the above-mentioned data, the possibility of post treatment deterioration should be addressed to the patients before initiation of radiotherapy. One of the important points highlighted in our study is that the…”
Section: Gandaglia Et Al Described Certain Clinicalmentioning
confidence: 99%